Treatment of methyl orange dye wastewater by cooperative electrochemical oxidation in anodic?cathodic compartment. - Pang, L.
Electrochemical oxidation of methyl orange wastewater was studied using Ti/IrO2/RuO2 anode and a self-made Pd/C O2-fed cathode in the divided cell with a terylene diaphragm. The result indicated that the appropriate rate of feeding air improved the methyl orange removal efficiency. The discoloration efficiency of methyl orange in the divided cell increased with increasing current density. The initial pH value had some effect on the discoloration of methyl orange, which became not obvious when the pH ranged from 2 to 10. However, the average removal efficiency of methyl orange wastewater in terms of total organic carbon (TOC) can reach 89.3%. The methyl orange structure had changed in the electrolytic process, and the characteristic absorption peak of methyl orange was about 470 nm. With the extension of electrolysis time, the concentration of methyl orange gradually reduced; wastewater discoloration rate increased gradually. The degradation of methyl orange was assumed to be cooperative oxidation by direct or indirect electrochemical oxidation at the anode and H2O2, ·OH, O2−· produced by oxygen reduction at the cathode in the divided cell. Therefore, the cooperative electrochemical oxidation of methyl orange wastewater in the anodic?cathodic compartment had better degradation effects.
Keywords: Dye wastewater; Electrochemical oxidation; Methyl orange; Pd/C O2-fed cathode